welseyyaidoo
welseyyaidoo
16-03-2024
Mathematics
contestada
3x-y=4,y=6-2x Substitution
Respuesta :
Helsh
Helsh
16-03-2024
Solution,
Given,
3x-y=4…..equation 1
y=6-2x
Putting the value of y in equation 1
3x-(6-2x)=4
3x-6+2x-4=0
5x-10=0
5(x-2)=0
x=2
Now,
y= 6-2x
y=2
Answer Link
VER TODAS LAS RESPUESTAS ( 44+ )
Otras preguntas
A group of students working in a high school chemistry lab believe they have discovered a new element! How exciting! Upon further testing by scientists (with b
HELP PLEASE!!!!!!!!!! A model rocket is launched with an initial upward velocity of 204 ft/s. The rocket's height h (in feet) after t seconds is given by the fo
A 200.0-g copper cylinder at 500°C is placed on a large block of ice at 0.00°C. Assume that no energy is transferred to the surroundings. What is the mass of
identify the region held by Britain that helped it control the shortest route from Europe to Asia.
Mental health professionals such as What do psychiatrists do
how to Determine the domain of the relation shown in a table
8. The number of pies sold by the Chipper Bakery is of the number of cookies sold by the Yummy Cookie Company. If both businesses sell 16 more of items, the Chi
how do I algebraically solve |4x-3|=5√(x+4)
Which expression is equivalent to p·q·q·q·q·q·q·q·q·q? 1. pq^9 2. 9pq 3. (pq)^9 4. (pq)^10
Please solve the question and chose from the provided answer options.
ACCESS MORE